2008
DOI: 10.1128/aem.00537-08
|View full text |Cite
|
Sign up to set email alerts
|

Fate of the Nitrilotriacetic Acid-Fe(III) Complex during Photodegradation and Biodegradation by Rhodococcus rhodochrous

Abstract: Aminopolycarboxylic acids are ubiquitous in natural waters and wastewaters. They have the ability to form very stable water-soluble complexes with many metallic di-or trivalent ions. The iron complex nitrilotriacetic acid-Fe(III) (FeNTA) has been previously shown to increase drastically the rate of photo-and biodegradation of 2-aminobenzothiazole, an organic pollutant, by Rhodococcus rhodochrous. For this paper, the fate of FeNTA was investigated during these degradation processes. First, it was shown, using i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…Indeed 99% of ABT was degraded after 25 h in the combined systems while 37% and 26% of ABT were photo-and biodegraded after 125 h, respectively. In order to understand better which mechanisms were responsible for this improvement of ABT degradation rate, the fate of FeNTA was investigated (Bunescu et al, 2008b). It was shown that FeNTA was transported and biotransformed inside the cell and/or phototransformed in the presence of sunlight (Bunescu et al, 2008b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed 99% of ABT was degraded after 25 h in the combined systems while 37% and 26% of ABT were photo-and biodegraded after 125 h, respectively. In order to understand better which mechanisms were responsible for this improvement of ABT degradation rate, the fate of FeNTA was investigated (Bunescu et al, 2008b). It was shown that FeNTA was transported and biotransformed inside the cell and/or phototransformed in the presence of sunlight (Bunescu et al, 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…In order to understand better which mechanisms were responsible for this improvement of ABT degradation rate, the fate of FeNTA was investigated (Bunescu et al, 2008b). It was shown that FeNTA was transported and biotransformed inside the cell and/or phototransformed in the presence of sunlight (Bunescu et al, 2008b). The same products were obtained during the photo-and biodegradation processes of FeNTA, including IDA (iminodiacetic acid), glycine and formate, probably because they both involve oxidoreduction mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Light had no direct effect on R. rhodochrous and the photoproducts issued from the transformation of ABT and FeNTA; in particular, • OH radicals issued from FeNTA phototransformation (Abida et al. 2006; Bunescu et al. 2008b) do not present any toxic effect for the energetic metabolism of micro‐organisms.…”
Section: Resultsmentioning
confidence: 97%
“…2009). Finally, Bunescu et al. (2008b) showed that this strain was also able to transform Fe(III)NTA into Fe(II), IDA (iminodiacetic acid), glycine and formate.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation